2020
DOI: 10.3389/fmed.2020.00073
|View full text |Cite
|
Sign up to set email alerts
|

Oral Probiotics Alleviate Intestinal Dysbacteriosis for People Receiving Bowel Preparation

Abstract: Background: Bowel preparation is necessary for successful colonoscopy, while it can seriously affect intestinal microbial composition and damage the intestinal mucosal barriers in humans.Methods: To figure out whether probiotics can sustain intestinal homeostasis and guard people's health, the probiotic drug of Bifidobacterium Tetragenous viable Bacteria Tablets (P group, n = 16) or placebo (C group, n = 16) was used for volunteers receiving bowel preparation, and high-throughput sequencing method was applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“…Previous studies have shown that the decrease in the abundance of Bacteroides is closely related to poor health. Moreover, butyrate produced by Bacteroides plays an important role in maintaining the intestinal health of the host, exerting immunity, and anti-tumor effects ( Deng et al, 2020 ). In addition to these two stains, we confirmed important relative abundance of several microbial flora before and after CACC558 treatment in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the decrease in the abundance of Bacteroides is closely related to poor health. Moreover, butyrate produced by Bacteroides plays an important role in maintaining the intestinal health of the host, exerting immunity, and anti-tumor effects ( Deng et al, 2020 ). In addition to these two stains, we confirmed important relative abundance of several microbial flora before and after CACC558 treatment in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…FBD patients suffered an increase in the Firmicutes to Bacteroidetes ratio [ 32 , 33 ], and an increase in the Firmicutes to Bacteroidetes ratio may pose a potential risk to patients' health [ 34 ]. In our study, comparing with the control group, the Firmicutes to Bacteroidetes ratio (a reducing trend of Firmicutes abundance and a significant increase of Bacteroidetes abundance at the level of phylum) in the probiotics group significantly reduced after 4 weeks of live combined Bacillus subtilis and Enterococcus faecium supplementation, with significantly reducing abundance of Ruminococcus , Fusicatenibacter , and Eubacterium hallii group (Firmicutes) at the level of genus, which might help to improve the FBD patients' health.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, comparing with the control group, the Firmicutes to Bacteroidetes ratio (a reducing trend of Firmicutes abundance and a significant increase of Bacteroidetes abundance at the level of phylum) in the probiotics group significantly reduced after 4 weeks of live combined Bacillus subtilis and Enterococcus faecium supplementation, with significantly reducing abundance of Ruminococcus , Fusicatenibacter , and Eubacterium hallii group (Firmicutes) at the level of genus, which might help to improve the FBD patients' health. Bacteroidetes play a vital role in degrading complex polysaccharides of cellulose, pectin, and xylan, which can help people absorb more energy from the diet, and butyrate produced by Bacteroidetes plays an important role in maintaining the intestinal health of the host, exerting immunity, and antitumor effect [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anaerobes play a dominant role in the gastrointestinal tract, among common anaerobes, Bifidobacterium is a functional gut microbiota, which is widely used in the treatment of inflammatory gastrointestinal diseases such as ulcerative colitis ( 155 , 156 ). TME in a low oxygen state creates a good growth environment for anaerobic bacteria ( 157 ). A study indicated that the accumulation of Bifidobacterium in TME can significantly improve the anti-tumor effect of anti-CD47 immunotherapy, which depends on the STING signal and the type I IFN within DC ( 158 ).…”
Section: The Effect Of Gut Microbiota In Cancer Immunotherapymentioning
confidence: 99%
“…The key role of B. fragilis is to restore the anti-CTLA-4 treatment response associated with Th1 immune responses in tumor-draining lymph nodes. environment for anaerobic bacteria (157). A study indicated that the accumulation of Bifidobacterium in TME can significantly improve the anti-tumor effect of anti-CD47 immunotherapy, which depends on the STING signal and the type I IFN within DC (158).…”
Section: Anti-cd47 Therapymentioning
confidence: 99%